The books printed by Agustín de Paz for the bishopric of Oviedo (1555-1559): A case-study of a diocesan publishing project during the Council of Trent - Rial, Benito (Revista General de Información y Documentación, 2017)
In 1547, Cristóbal de Rojas and Sandoval ascended to the bishopric of Oviedo, and, shortly afterward, a major reform in the bishopric was begun. In 1550, its council had started to work on a new breviary, and, in 1553, an ambitious publishing project was put in place for reforming the diocese. This article brings together documentation kept at the Archivo de la Catedral de Oviedo, Archivo del Reino de Galicia, and Archivo Histórico Universitario de Santiago to narrate the details of the complex and uneven story of this project and the works printed by Augustin de Paz between 1555 and 1559 for it. The abundant documentation included in this article also provides many details of the production process of these works and the people involved and informs of the financing of the publishing project through the publication of indulgences and of their illegal market in a moment of religious convulsion.
Keywords: Cristóbal de Rojas; Agustín de Paz; Reform; Printing; Oviedo; Sixteenth century; Trent; breviary; Missal; Synod; Synodal costitutions; Bull; Indulgence; Liturgical book